Pengaruh Model PBL dengan Mengunakan Jarimatika terhadap Kemampuan Pemecahan Masalah Penjumlahan Kelas 1 SD Pandeanlamper 04 - Virgin, Novela Simpatika; Nursyahidah, Farida; Huda, Choirul (Universitas Muria Kudus, 2023)
This study aims to analyze the effect of the problem-based learning model using the Jarimatika method on the mathematical problem-solving abilities of grade 1 students at SD Pandeanlamper 04. This research is a quantitative study with a quasi-experimental type. The research design refers to the one-group pretest-posttest which only uses one group as the experimental class. The subjects of this study included 28 grade 1 students at SD Pandean Lamper 04. Data collection techniques with tests with instruments of pretest and posttest questions. As well as interviews as a preliminary study. Data analysis was done using the paired sample t-test with the help of SPSS 25. The prerequisite test showed that the pretest and posttest data were normally distributed because the sig value exceeded 0.05. The results showed that the Jarimatika method affected the problem-solving abilities of grade 1 students at SD Pandeanlamper 04. The results of the paired sample t-test were sig. 0.000 0.05 so it can be concluded that there is an average difference between the pretest and posttest in the test of students' mathematical problem solving abilities by applying the PBL learning model with Jarimatika for addition and the average mathematical problem solving ability of students by applying the PBL learning model with Jarimatika for addition was better than before the implementation of the PBL learning model with Jarimatika for addition.